Optimization of Logistics Warehouse in Supporting E-Commerce and Increasing MSME Sales: A Literature Review - Lermatan, Esterlinus Edwin; Silalahi, Tiur Mery B (Siber Journal of Transportation and Logistics, 2025)
The rapid growth of e-commerce in Indonesia has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt to more efficient distribution and logistics systems. Optimizing logistics warehouses is a crucial factor in supporting smooth supply chains, accelerating delivery, and increasing customer satisfaction. This literature review aims to identify relevant logistics warehouse optimization strategies in the context of MSME digitalization and the development of e-commerce. This article discusses the basic concepts of warehouse management, the application of technologies such as warehouse management systems (WMS), automation, and logistics integration with e-commerce platforms. In addition, the challenges faced by MSMEs in logistics management and solutions that can be applied to improve operational efficiency are also examined. The results of the review show that collaboration between MSMEs, logistics providers, and the use of digital technology play a significant role in increasing the competitiveness of MSMEs in the digital economy era.